THE ROLE OF ISLAMIC EDUCATION IN BUILDING RELIGIOUS MODERATION IN THE ERA OF SOCIAL POLARIZATION AND DIGITAL POLITICS - Supandi, Supandi; Aini, Kurratul (Universitas Islam Madura, 2025)
The rapid expansion of digital technology and social media has significantly changed communication, social interaction, and political dynamics in Indonesia. However, these developments have also intensified social and political polarization, often accompanied by hate speech, hoaxes, and politicization of religion. This study aims to analyze the role of Islamic education in promoting religious moderation as a response to the challenges of digital polarization. Using a qualitative phenomenological approach, the research was conducted in selected Islamic educational institutions, including madrasas, Islamic boarding schools, and Islamic universities, with purposive sampling of key actors such as educators, students, and community stakeholders. Data were collected through in-depth interviews, participatory observations, and document analysis, and analyzed using Miles & Huberman's interactive model with triangulation for validity. The findings reveal that Islamic education plays a strategic role in strengthening religious moderation through four main practices: (1) curriculum integration of the values of tolerance, peace, and citizenship; (2) digital literacy programs to counter misinformation and ideological propaganda; (3) extracurricular activities that encourage interfaith dialogue and social solidarity; and (4) the role of exemplary educators (teachers, kyai, and lecturers) in realizing wasathiyah values. The study concludes that Islamic education is not only a means of transmitting religious knowledge but also an important agent of social cohesion and national stability in the digital age.